Detailed pharmacognostical studies on Berberis aristata DC plant - Bhawana Rathi (Ancient Science of Life, 2013)
Background: Berberis aristata DC (Berberidaceae) commonly known in Hindi as "Dāruhaldi" and "Citra," is an important medicinal herb native to Northern Himalaya region. The plant is used traditionally in Indian system of medicine as an antibacterial, antiperiodic, antidiarrheal and anticancer and it is also used in the treatment of ophthalmic infections. Its root, stem and leaves also find their use in treatment of various ailments and hence is used extensively in Ayurveda. Materials and Methods: Samples of the whole plants of B. aristata were collected and identified. Hand and microtome sections were taken, stained and mounted and the cell content and cell wall structure were studied according to the method described by Kay and Johansen. Representative sketches were made with the help of camera Lucida. Methods for determining the quantitative values were the same as described elsewhere. For fluorescence analysis, the powder of the root, stem and leaf were examined under ultraviolet light. Total ash, acid insoluble ash and water-soluble ash values and water- and alcohol-soluble extractives were determined. Results: The detailed investigations carried on the pharmacognosy of the root; stem and leaf of B. aristata have brought out some salient diagnostic features, which allow one to differentiate it from other substitutes and or adulterants. The determination of quantitative values, fluorescence analysis and the use of lycopodium spore analysis has specifically contributed to this differentiation. Conclusion: From the foregoing observation on the pharmacognosy of root, stem and leaf of B. aristata DC, the salient diagnostic characters of three parts have been presented, which can allow one to differentiate it from other substitutes and or adulterants.